Tryptophan Metabolism in Bipolar Disorder in a Longitudinal Setting - Frederike T. Fellendorf; Johanna M. Gostner; Melanie Lenger; Martina Platzer; Armin Birner; Alexander Maget; Robert Queissner; Adelina Tmava-Berisha; Cornelia A. Pater; Michaela Ratzenhofer; Jolana Wagner-Skacel; Susanne A. Bengesser; et al. (MDPI AG, 2021)
Immune-mediated inflammatory processes and oxidative stress are involved in the aetiopathogenesis of bipolar disorder (BD) and weight-associated comorbidities. Tryptophan breakdown via indoleamine 2,3-dioxygenase-1 (IDO-1) along the kynurenine axis concomitant with a pro-inflammatory state was found to be more active in BD, and associated with overweight/obesity. This study aimed to investigate tryptophan metabolism in BD compared to controls (C), stratified by weight classes, in a longitudinal setting, dependent on the incidence of BD episodes. Peripheral tryptophan, kynurenine, and neopterin were assessed in the serum of 226 BD individuals and 142 C. Three samples in a longitudinal assessment were used for 75 BD individuals. Results showed a higher kynurenine/tryptophan in both BD compared to C and overweight compared to normal weight persons. Levels remained stable over time. In the longitudinal course, no differences were found between individuals who were constantly euthymic or not, or who had an illness episode or had none. Findings indicate that tryptophan, kynurenine, and IDO-1 activity may play a role in pathophysiology in BD but are not necessarily associated with clinical manifestations. Accelerated tryptophan breakdown along the kynurenine axis may be facilitated by being overweight. This may increase the risk of accumulation of neurotoxic metabolites, impacting BD symptomatology, cognition, and somatic comorbidities.